La publicidad televisiva como herramienta promocional de productos elaborados en cerámica por la asociacion de mujeres artesanas Divino Niño del barrio Cera perteneciente a la parroquia Taquil del cantón Loja y su posicionamiento en el mercado consumidor local, periodo julio diciembre de 2013. Propuesta alternativa - Rojas Paladines, José Tomas (2015)
This research main objective was to ascertain what communication and promotion tool used by the Association of Women Artisans Divine Child Cera neighborhood, the parish of Canton Loja Taquil to position its elaborate on clay in the local market. For the development of the subject methods are used for scientific purposes, to collect information inherent in the subject, then the application of surveys and interviews to learn how to promote the products of ceramics, the observation was a key ally possible to distinguish the way they do for the promotion of products made of ceramics, the universe was studied 100 people who provided reliable way to advance the process of investigation and to propose alternatives solution. Through field investigation it was found that the only way to promote these objects is through advertising from person to person, ie those who have acquired ceramic crafts. The higher incidence determined conclusion, it is necessary to use a television as a communication tool to promote the finished ceramic products Wax neighborhood. The opinion of the lojana citizenship also made a big importance because it would be necessary to state that the promotion or dissemination of crafts made by local mass media, especially television